HPV16 seropositivity and subsequent HPV16 infection risk in a naturally infected population: comparison of serological assays. - Shih-Wen Lin; Arpita Ghosh; Carolina Porras; Sarah C Markt; Ana Cecilia Rodriguez; Mark Schiffman; Sholom Wacholder; Troy J Kemp; Ligia A Pinto; Paula Gonzalez; Nicolas Wentzensen; Mark T Esser; et al. (PLoS ONE, 2013)
Several serological assays have been developed to detect antibodies elicited against infections with oncogenic human papillomavirus (HPV) type 16. The association between antibody levels measured by various assays and subsequent HPV infection risk may differ. We compared HPV16-specific antibody levels previously measured by a virus-like particle (VLP)-based direct enzyme-linked immunoassay (ELISA) with levels measured by additional assays and evaluated the protection against HPV16 infection conferred at different levels of the assays.Replicate enrollment serum aliquots from 388 unvaccinated women in the control arm of the Costa Rica HPV vaccine trial were measured for HPV16 seropositivity using three serological assays: a VLP-based direct ELISA; a VLP-based competitive Luminex immunoassay (cLIA); and a secreted alkaline phosphatase protein neutralization assay (SEAP-NA). We assessed the association of assay seropositivity and risk of subsequent HPV16 infection over four years of follow-up by calculating sampling-adjusted odds ratios (OR) and HPV16 seropositivity based on standard cutoff from the cLIA was significantly associated with protection from subsequent HPV16 infection (OR = 0.48, CI = 0.27-0.86, compared with seronegatives). Compared with seronegatives, the highest seropositive tertile antibody levels from the direct ELISA (OR = 0.53, CI = 0.28-0.90) as well as the SEAP-NA (OR = 0.20, CI = 0.06, 0.64) were also significantly associated with protection from HPV16 infection.Enrollment HPV16 seropositivity by any of the three serological assays evaluated was associated with protection from subsequent infection, although cutoffs for immune protection were different. We defined the assays and seropositivity levels after natural infection that better measure and translate to protective immunity.